BMI and low vitamin D are causal factors for multiple sclerosis: A Mendelian Randomization study. Issue 2 (March 2020) - Jacobs, Benjamin M.; Noyce, Alastair J.; Giovannoni, Gavin; Dobson, Ruth
Abstract : Objective: To update the causal estimates for the effects of adult body mass index (BMI), childhood BMI, and vitamin D status on multiple sclerosis (MS) risk. Methods: We used 2-sample Mendelian randomization to determine causal estimates. Summary statistics for SNP associations with traits of interest were obtained from the relevant consortia. Primary analyses consisted of random-effects inverse-variance-weighted meta-analysis, followed by secondary sensitivity analyses. Results: Genetically determined increased childhood BMI (ORMS 1.24, 95% CI 1.05–1.45, p = 0.011) and adult BMI (ORMS 1.14, 95% CI 1.01–1.30, p = 0.042) were associated with increased MS risk. The effect of genetically determined adult BMI on MS risk lessened after exclusion of 16 variants associated with childhood BMI (ORMS 1.11, 95% CI 0.97–1.28, p = 0.121). Correcting for effects of serum vitamin D in a multivariate analysis did not alter the direction or significance of these estimates. Each genetically determined unit increase in the natural-log-transformed vitamin D level was associated with a 43% decrease in the odds of MS (OR 0.57, 95% CI 0.41–0.81, p = 0.001). Conclusions: We provide novel evidence that BMI before the age of 10 is an independent causal risk factor for MS and strengthen evidence for the causal role of vitamin D in the pathogenesis of MS.